1973
DOI: 10.1007/bf01645976
|View full text |Cite
|
Sign up to set email alerts
|

Local normality in Quantum Statistical Mechanics

Abstract: It is shown that K.M.S.-states are locally normal on a great number of C*-algebras that may be of interest in Quantum Statistical Mechanics. The lattice structure and the Choquet-simplex structure of various sets of states are investigated. In this respect special attention is payed to the interplay of the K.M.S.-automorphism group with other automorphism groups under whose action K.M.S.-states are possibly invariant. A seemingly weaker notion than G-abelianness of the algebra of observables, namely G'abeliann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Takesaki and Winnink [44] have shown that a locally normal state decomposes into locally normal states, if the split property holds. We shall show here analogous results for localizable representations (sectors).…”
Section: Disintegration Of Locally Normal Representations and Of Sementioning
confidence: 99%
“…Takesaki and Winnink [44] have shown that a locally normal state decomposes into locally normal states, if the split property holds. We shall show here analogous results for localizable representations (sectors).…”
Section: Disintegration Of Locally Normal Representations and Of Sementioning
confidence: 99%
“…By the argument in the appendix of [14], the fact that ω ξ A 0,ι (O ) = ω 0,ι A 0,ι (O ), together with translation covariance of π ξ , imply (8.4) if it is known that property B holds in the representation π ξ . But if H vac 0,ι is separable, then each local algebra π vac 0,ι (A 0,ι (O)) has a separable predual, and being ω ξ locally normal, from [36,Corollary 3.2] it follows that the Hilbert space H ξ of π ξ is separable, and then, by the already recalled argument of Roberts [32], property B holds in the representation π ξ .…”
mentioning
confidence: 99%
“…This set K( * ∞ 1 A, * ∞ 1 σ) is a compact affine set in the weak * -topology and is known to be a Choquet simplex whose extreme points are those φ ∈ K( * ∞ 1 A, * ∞ 1 σ), the von Neumann algebras generated by images of whose GNS-representations are factors (cf. [5], [9] and [11]).…”
Section: The Simplex Of Kms Quantum Symmetric Statesmentioning
confidence: 99%